2018
DOI: 10.1371/journal.pone.0207322
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health disparities among U.S. long-haul truck drivers: the influence of work organization and sleep on cardiovascular and metabolic disease risk

Abstract: ObjectiveThe organization of work has undergone vast transformations over the past four decades in the United States and has had profound impacts on worker health and wellbeing. The profession of commercial truck driving is one of the best examples. Particularly for long-haul truck drivers, changes in work organization have led to disproportionately poor physiological, psychological, and sleep health outcomes.MethodsThe present study examined disparities in cardiometabolic disease risk among long-haul truck dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 102 publications
3
79
2
4
Order By: Relevance
“…These patterns could eventually be elicited more easily if the individual was exposed to such stimuli with high frequency or regularity [58]. The occupational context, more specifically, can be described as an ideal scenario for the prevention and training of everything that concerns coping with stress, emotional exhaustion at work and other relevant factors that may influence outcomes in driving safety, such as fatigue and adequate recovery of workers [31,59]. This is due to two facts: first, work is one of the vital scenarios in which stress is most prevalent, and second, it is a potential source of good interventions that may result in lower rates of occupational diseases, work fatigue, and accidents, both inside and outside of the workplace [56,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns could eventually be elicited more easily if the individual was exposed to such stimuli with high frequency or regularity [58]. The occupational context, more specifically, can be described as an ideal scenario for the prevention and training of everything that concerns coping with stress, emotional exhaustion at work and other relevant factors that may influence outcomes in driving safety, such as fatigue and adequate recovery of workers [31,59]. This is due to two facts: first, work is one of the vital scenarios in which stress is most prevalent, and second, it is a potential source of good interventions that may result in lower rates of occupational diseases, work fatigue, and accidents, both inside and outside of the workplace [56,60].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the existing evidence in the working population, EEW has already been related to different adverse health consequences such as: depressive and anxious disorders [26,27], systematic headaches [28], a greater Odds Ratio (OR) for developing hypertension [29] gastrointestinal diseases [30], musculoskeletal disorders [28], acute/chronic fatigue [31,32], numerous sleep problems [33][34][35], and a lower performance at work, in comparison to workforce groups that, on the other hand, have not reported burnout symptoms [36,37]. Empirically, some studies have found that burnout-related issues, such as EEW, may explain higher rates of job absenteeism and consistent turnover rates of workers [6,38,39], including the case of professional drivers, whose stressful work environment and role conflicts seem to be closely related to the appearance and prevalence of burnout-related symptomatology and other negative occupational and health outcomes [40,41].…”
Section: Associations Between Emotional Exhaustion At Work Health Anmentioning
confidence: 99%
“…The demographic makeup of the truck driver sample has been reported in our previous published studies Hege et al, 2016;Hege et al, 2017;Hege, Lemke, Apostolopoulos, & Sönmez, 2018;. The descriptive characteristics, in relation to work organization characteristics, of the driver sample are presented in Table 1.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…10 As an example, data from the National Health and Nutrition Examination Survey (NHANES) study showed that truck drivers have lower levels of physical activity, increased body mass index, lower HDL cholesterol, increased cardiovascular disease and more mental health challenges. 24 These data can be used to support clinical and public health measures to support these higher risk population. 25 Teaching strategies for nutrigenetics and nutrigenomics To keep up with research advancement, different strategies within medical nutrition education need to be considered, such as the inclusion of nutrigenetics and nutrigenomics.…”
Section: Case Examples Of Data-driven Decisionsmentioning
confidence: 99%